Transcultural validation of the basic empathy scale for children in Arabic language: psychometric properties among schoolchildren in Tunisia - Chokri, Imed; Peyrotte, Marianne; Zanna, Omar; Jarraya, Mohamed (Frontiers in Education, 2024)
IntroductionTo date, there is no empathy test specifically designed in the Arabic language for children. When administered in the Arab world, these tests are often provided in French or English, known to induce numerous intercultural biases.AimThe objective of our study is to, for the first time, propose a translation and validation of the Basic Empathy Scale for Children in the Arabic language.MethodFive hundred and thirty three Tunisian schoolchildren (age = 10.15 ± 1.39 years, 55.2% girls and 44.8% boys) participated voluntarily in the study. The students answered tow scales that measure the Empathy and the social desirability.ResultThe Arabic version of the BES-C demonstrated a 3-factor structure: cognitive empathy, emotional contagion, and emotional disconnection previously observed in other cultural contexts. McDonald’s omega is 0.72 for the Arabic version of the BES-C. The test–retest intra-class correlation coefficient over six weeks (n = 180) was 0.67. The findings show an increase in cognitive empathy with age, stability in emotional contagion, and a gradual decrease in emotional disconnection. Girls scored higher in emotional contagion, while boys showed a slight predominance of emotional disconnection. No significant gender differences were found in cognitive empathy.ConclusionThe Arabic version of the BES-C is a dependable tool for evaluating empathy in Arabic-speaking children, paving the way for its use in cross-cultural research and specialized interventions.